2020
DOI: 10.1038/s41419-020-03000-z
|View full text |Cite
|
Sign up to set email alerts
|

Bip inhibition in glioma stem cells promotes radiation-induced immunogenic cell death

Abstract: Tumor regression in sites distant to the irradiated field are thought to be associated with emission of damage-associated molecular patterns (DAMPs) molecules and generation of immunogenic cell death (ICD). Glioma stem cells (GSCs) are resistant to high doses of radiation, and ultimately select the outgrowth of a more aggressive tumor. This study showed high-dose IR triggered fewer DAMPs molecules exposure and release in GSCs comparing to matched non-GSCs. Downregulation of binding immunoglobulin protein (Bip)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…However, certain cancer cell autonomous mechanisms regulating proteostasis can either subvert danger signaling pathways (like the PERK-eiF2α axis [ 66 ]), cause retention of DAMPs thereby impairing the proficient dialogue between dying cancer cells and the immune system or secrete mutate forms of DAMPs (like mutant CRT) which supposed to act as a decoy for DCs in the wild-type [ 67 ]. For example, in glioma Bip upregulation, a typical marker of the activation of the unfolded protein response, restricted DAMPs exposure and release in glioma stem cells [ 68 ]. A recent study also reported that cancer cells may avoid the exposure of CRT through a mechanism involving stanniocalcin-1 mediated retention of CRT in the cytoplasm (thus suggesting a pool of cytosolic CRT), a process that impairs phagocytosis by antigen-presenting cells and subsequent anticancer adaptive immunity [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, certain cancer cell autonomous mechanisms regulating proteostasis can either subvert danger signaling pathways (like the PERK-eiF2α axis [ 66 ]), cause retention of DAMPs thereby impairing the proficient dialogue between dying cancer cells and the immune system or secrete mutate forms of DAMPs (like mutant CRT) which supposed to act as a decoy for DCs in the wild-type [ 67 ]. For example, in glioma Bip upregulation, a typical marker of the activation of the unfolded protein response, restricted DAMPs exposure and release in glioma stem cells [ 68 ]. A recent study also reported that cancer cells may avoid the exposure of CRT through a mechanism involving stanniocalcin-1 mediated retention of CRT in the cytoplasm (thus suggesting a pool of cytosolic CRT), a process that impairs phagocytosis by antigen-presenting cells and subsequent anticancer adaptive immunity [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that Bip expression is associated with increased tumor progression ( 96 ). Accordingly, Bip inhibition can inhibit tumor growth by enhancing ER stress to elicit cDAMPs release or exposure to activate antitumor immunity ( 78 ). The combination of Bip inhibition and 10 Gy IR enhanced IR-induced ICD with increased CRT exposure, ATP secretion, and HMGB1 release and promoted the phagocytosis and maturation of DCs.…”
Section: The Methods Of Enhancing Ir-induced Icdmentioning
confidence: 99%
“…The combination of Bip inhibition and 10 Gy IR enhanced IR-induced ICD with increased CRT exposure, ATP secretion, and HMGB1 release and promoted the phagocytosis and maturation of DCs. As a vaccine, glioma stem cells treated with Bip inhibition and IR could delay tumor generation efficiently, facilitate the proliferation of CD4 + and CD8 + T cells, and decrease Treg cell infiltration in vivo ( 78 ).…”
Section: The Methods Of Enhancing Ir-induced Icdmentioning
confidence: 99%
“…Indeed, gliomas do present high levels of glycolysis, also due to the hypoxia, which supports tumor growth, and this mechanism may be regulated by PERK and the activation of Akt signaling ( Hou et al, 2015 ). The inhibition of upstream effectors of PERK sensitizes GSCs to radiotherapy and decreases recurrence ( Yang et al, 2020 ). Furthermore, PERK modulates angiogenesis in GBM in hypoxic conditions ( Soni et al, 2020 ), and it is correlated with the stem-like cell phenotype through the modulation of SOX2 expression ( Penaranda-Fajardo et al, 2019 ).…”
Section: Unconventional Protein Secretion In Brain Tumorsmentioning
confidence: 99%